Deconstructive Critique of the Story «Cirios Rojos» by Segundo Serrano Poncela - Emire Zeynep Önal (Litera: Dil, Edebiyat ve Kültür Araştırmaları Dergisi)
This paper analyses the story «Cirios rojos» by Segundo Serrano Poncela from a deconstructive perspective. Segundo Serrano Poncela wrote the story during his exile in Latin America and tells an event that occurred at the beginning of the military conflict of 1936. The story pits members of the two sides of the Spanish Civil War, a devout woman and a Republican man, against each other in a life-and-death struggle. Serrano Poncela presents an inside observation of the thoughts and feelings of his characters and brings out their different visions. The unforeseen confrontation of the two adversaries becomes a conflict between them; the devout woman wishes to expel the republican as her enemy; he is dependent on her help. The woman’s house becomes a battlefield for them, where one wants to save herself from the presence of the other, and the other wants to save his life. The text constructs a hierarchical opposition between the two; it elevates one and lowers the other, underlining the inherent characteristics of the two points of view. Focusing on significant points in the text, we try to show how the higher side of the hierarchy overthrows its own logical system, falling into contradictions between what it stands for and what it does.